Pelaksanaan Inovasi Kebijakan Pendirian Rumah Restorative Justice Pada Tingkat Desa di Kabupaten Madiun - Sugiarto, Kantrey; Udjiwati, Lulus; Anwar, Khoyrul (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2023)
One of the regions that has implemented restorative justice policy innovation is Madiun Regency. This policy aims to be an alternative to solving criminal cases at the village level through deliberation. This study aims to determine the prospects for implementing policy innovations for the establishment of restorative justice houses in Madiun Regency. This study used a qualitative descriptive approach. Data analysis is carried out interactively through (a) data collection; (b) data assessment; (c) interpretation of data; and (d) data inference. The results showed that: (1) restorative justice houses in Madiun Regency can be implemented properly at the village level, taking into account the conditions of cases and perpetrators; (2) Taking case resolution can be through the restorative justice house is the desire to reconcile and cases in the category of not minor crimes, with a deliberative mediation process; 3) Restorative justice houses are also implemented based on restoring losses, both losses suffered by victims and losses borne by the community; 4) The implementation of restorative justice policy can be said to have been carried out ideally, involving at least three stakeholders, namely, victims, perpetrators, and civil society or society in determining the resolution of cases.